Using The Irrigation Water Quality Index to Evaluate of Some Water Resources in Al-Abyar-Ghut Al-Sultan Area NE Libya. - Imneisi, Idris Basher (Scientific Journal of University of Benghazi, 2021)
In arid and semi-arid regions around the world, water quality and quantity are essential in agricultural systems. This study aimed to evaluate the quality of irrigation water in Al-Abyar area (Ghout Al-Sultan) for agricultural purposes using the Irrigation Water Quality Index (IWQI). During the rainy season, thirty-three water samples were collected from 11 government wells in the Ghout al-Sultan area with an average of 3 samples per well from January to March 2021. As a result, the irrigation water quality index (IWQI) was calculated using the values of electrical Conductivity (EC (, Sodium Adsorption Rate (SAR), Sodium (Na), Chloride (Cl), and Bicarbonate (HCO3). The irrigation water quality index (IWQI) was classified in the study area as having medium quality for irrigation water use (63. 5%). The current study demonstrated determination of the quality of some water sources in this area using an irrigation water quality index. It suggests that the irrigation water quality of the study area can depending on soil and crop conditions in the field of irrigation water quality management.